Consistent trajectories of rhinitis control and treatment in 16,177 weeks - Sousa-Pinto, Bernardo (2022)
Funding Information: MASK‐air® has been supported by EU grants (POLLAR, EIT Health; Structural and Development Funds, Twinning, EIP on AHA and H2020) and educational grants from Mylan‐Viatris, ALK, GSK, Novartis and Uriach. Publisher Copyright: © 2022 The Authors. Allergy published by European Academy of Allergy and Clinical Immunology and John Wiley & Sons Ltd.